A Comprehensive Study of the Anatomical Variations of the Posterolateral Tubercle of Talus - Kalbouneh,Heba (Sociedad Chilena de Anatomía, 2021)
SUMMARY: The aim of our study was to determine the prevalence and the anatomical variations of the posterolateral tubercle of talus in relation to sex on CT imaging. A total of 1478 ankle CT scans was retrospectively reviewed for the different anatomical variants of the posterolateral tubercle of talus, the type and size of os trigonum. Normal sized lateral tubercle was found in 46.1 %, an enlarged posterolateral tubercle (Stieda’s process) in 26.1 %, os trigonum in 20.5 % and almost absent tubercle in 7.3 %. A statistically higher prevalence of Stieda’s process was found in males while os trigonum was higher in females (p<0.05). Among feet with os trigonum, 25.7 % were non-articulating and identified as a separate bone located posterior to the posterolateral tubercle of talus and 74.3% of os trigonum were identified as fused to the posterolateral tubercle by synchondrosis or syndesmosis. Additionally, 17.5 % of os trigonum were associated with intact lateral tubercle, 53.5 % were considered as part of the lateral tubercle and 29.0 % were without a lateral tubercle. According to its size, 22.8 % of os trigonum were smaller than 0.5 cm, 55.4 % were between 0.5 and 1cm, and 21.8 % were larger than 1 cm. No significant differences were found between the different types/sizes of os trigonum according to gender (p>0.05). The posterolateral tubercle of talus and its accessory ossicle, the os trigonum, could vary morphologically. The data of this study could be helpful in understanding the clinical problems that could be associated with some of these variants.